Analisis Kinerja Pembangunan Daerah Otonom Baru di Indonesia Tahun 2010-2014: Profil dan Determinan - Lambang Haris Wijayanto; Muhamad Fathul Muin (CV. Literasi Indonesia, 2020)
This research is motivated by the high interest of the people and the People's Representative Council (PRC) to make their regional autonomous. On the other hand, according to the Ministry of the Interior of the New Autonomous Region, the results of the autonomous region still failed to develop. To see the welfare of the people in the region resulting from the autonomous, researchers tried to look at it based on the results of regional macro development. Therefore, a Regional Development Index (RDI) constructed, which uses the factor analysis weighting method. RDI can be used to see the achievements of the regional development in Indonesia by looking at the comparison of development outcomes. So that RDI can see the development performance of the new autonomous regency/city and see the comparison with the origin regency/city. Besides, researchers looked at the effect of the share of mining Regional-GDP, the share of agricultural Regional-GDP, the average length of school for workers (ALSW), the percentage of roads in a minimum good condition and the growth of regional original income (ROI) to development performance in the autonomous regency/city using the method of regression analysis with panel data. Based on the results obtained, development in the area of new autonomy is not much different from the development in the origin area. Also, the average length of school for workers (ALSW) and minimum road percentage both have positive and significant effects on RDI, while the share of agricultural GRDP has a negative and significant effect on RDI.